Do brood parasitic Common Cuckoos develop brood patches during the breeding season? - Jun-Seo Go; Hae-Ni Kim; Sue-Jeong Jin; Myeong-Chan Cha; Heesoo Lee; Jin-Won Lee (Avian Research, 2024)
Many birds develop brood patches on their ventral apterium under hormonal regulation to effectively transmit body heat to eggs during incubation. The developed patch has several characteristics, including de-feathering, vascularization, and edema. However, little is known about whether avian brood parasites that do not incubate their eggs exhibit brood patch development during the breeding season. In this study, we measured the size of the ventral apterium in 114 Common Cuckoos (Cuculus canorus) captured in the field throughout the breeding season and examined the appearance of the ventral apterium to confirm the development of brood patches. We also examined whether morphological traits and various factors correlated with the size of the ventral apterium (sternal apterium and abdominal apterium) and how it changed during the breeding season. We found no clear signs of brood patch development in Common Cuckoos captured throughout the breeding season, indicating that they likely did not develop brood patches on the ventral apterium during this period. We also found that ventral apterium size was positively correlated with wing length and body weight. In addition, Common Cuckoos with newly growing feathers on the boundary of the ventral apterium with pteryla were frequently observed as seasons progressed to the end. In conclusion, Common Cuckoos exhibit neither brood patch development nor the vestigial characteristics of ancestral brood patches, except for the growth of feathers on boundary the ventral apterium. Further studies examining brood patches across different groups of avian brood parasites are valuable for enhancing our understanding of the developmental and physiological adaptations of avian brood parasites.